(untitled) (UKLO Proceedings, 2025)
This research paper investigates how restorative justice can promote sustainability and prevent recidivism while prioritizing victim reparation and inclusion, focusing on its potential impact on achieving Sustainable Development Goal 16, which pertains to peace, justice, and inclusive institutions. The study employs secondary data collection to analyse existing literature, case studies, and relevant data sources to evaluate the efficacy of restorative justice methods. The findings indicated that restorative justice prioritizes victim-centred processes, offender accountability, and community engagement, which improved victim well-being and a reduction in recidivism rates. The methods of Encounter, Repair and Transform were identified as essential components for setting up meaningful communication between victims and offenders, addressing the inflicted harm, and promoting community reintegration. The research highlighted that justice aids equitable access to justice for all, including marginalised populations, while cultivating accountable and inclusive institutions. By addressing the root causes of crime and promoting social inclusion, Restorative justice contributes to sustainable peace and development. The study concluded that empirical evidence supports the notion that restorative justice practices can effectively meet the objectives of SDG 16, reinforcing the interconnectedness of justice, peace, and inclusion.